2018
DOI: 10.1007/s00604-018-2738-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vanillin by using gold nanoparticle-modified screen-printed carbon electrode modified with graphene quantum dots and Nafion

Abstract: A voltammetric analytical assay for the selective quantification of vanillin is described. It is based on the use of a gold nanoparticle-modified screen-printed carbon electrode (SPCE) modified with graphene quantum dots (GQD) in a Nafion matrix. The GQD were synthesized by an acidic thermal method and characterized by UV-Vis, photoluminescence, and FTIR spectroscopy. The modified SPCE displays a strongly enhanced response to vanillin. Linear sweep voltammetry (LSV) and differential pulse voltammetry (DPV) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Also, electrochemical techniques receive significant attention due to their unique properties such as high selectivity, low cost, sensitivity, operational simplicity, and fast response [1,[6][7][8]. Over the last ten years, the quick development in the electrochemical determination of vanillin has become a new choice [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, electrochemical techniques receive significant attention due to their unique properties such as high selectivity, low cost, sensitivity, operational simplicity, and fast response [1,[6][7][8]. Over the last ten years, the quick development in the electrochemical determination of vanillin has become a new choice [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study of carbon nanomaterials to improve electrode sensitivity as a direct result of their enhanced electron transfer kinetics and the improved surface areato-volume ratio has kept materials scientists fascinated for the last two decades [51,52]. Graphene, the 2D carbon nanomaterial along with its oxides (graphene oxide) and other carbon nanoparticles including carbon nanotubes, carbon black, onion-like carbon and carbon dots have all been incorporated into electrochemical sensing applications [51][52][53][54][55][56][57]. In particular, the ability to improve paperelectrode sensitivity and selectivity through gold nanoparticle decorated graphenes has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the electrochemical determination of vanillin, various types of electrodes and modified electrodes have been successfully used. For example, gold nanoparticlemodified screen-printed carbon electrode modified with graphene quantum dots and Nafion [12], overoxidized poly(pyrrole) film-modified glassy carbon electrode [13], Aluminum doped TiO2 nanoparticles-modified screen printed carbon electrode [14], AuPd nanoparticlesgraphene composite modified electrode [23] and screen printed graphite electrode [26] have been used for the determination of vanillin using differential pulse or square wave voltammetric techniques. However, our literature search showed that recently often preferred pencil graphite electrode (PGE) has not been used for the determination of vanillin.…”
Section: Introductionmentioning
confidence: 99%
“…In the determination of vanillin a variety of methods have been developed using chromatographic [5][6][7][8], spectroscopic [3,9,10] and electroanalytical techniques [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although chromatographic methods such as GC and HPLC with various detectors (especially MS detector) have been widely used for the selective and reliable detection of vanillin [5][6][7][8], they have some drawbacks such as time consuming sample pretreatment procedures, high cost, expensive devices, high consumption of organic solvent, needs highly trained personal etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation